2015
DOI: 10.1007/s11065-015-9292-y
|View full text |Cite|
|
Sign up to set email alerts
|

Appraising the Role of Iron in Brain Aging and Cognition: Promises and Limitations of MRI Methods

Abstract: Age-related increase in frailty is accompanied by a fundamental shift in cellular iron homeostasis. By promoting oxidative stress, the intracellular accumulation of non-heme iron outside of binding complexes contributes to chronic inflammation and interferes with normal brain metabolism. In the absence of direct non-invasive biomarkers of brain oxidative stress, iron accumulation estimated in vivo may serve as its proxy indicator. Hence, developing reliable in vivo measurements of brain iron content via magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 166 publications
(286 reference statements)
8
89
2
3
Order By: Relevance
“…The cumulative record thus far supports the proposition that brain iron accumulation may be a meaningful biomarker of impending structural and cognitive declines in aging and disease (Schenck and Zimmerman 2004; Walsh et al 2013; Ward et al 2014; Daugherty and Raz 2015). Nonetheless, the temporal relationship between iron accumulation and structural changes in the brain is unclear.…”
Section: 0 Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…The cumulative record thus far supports the proposition that brain iron accumulation may be a meaningful biomarker of impending structural and cognitive declines in aging and disease (Schenck and Zimmerman 2004; Walsh et al 2013; Ward et al 2014; Daugherty and Raz 2015). Nonetheless, the temporal relationship between iron accumulation and structural changes in the brain is unclear.…”
Section: 0 Introductionmentioning
confidence: 54%
“…Although the sample was, on average, normotensive, in the course of study, as many as 11 participants had clinically diagnosed or observed hypertension (blood pressure measurement at least 140 mm Hg systolic or 90 mmHg diastolic; see Table 1). Hypertension was determined categorically at each assessment and composited into a frequency score—ranging 0 (normotensive at all assessments) to 1 (hypertensive at all assessments)—that was tested as a cardiovascular risk factor to potentially explain age-related variability in iron accumulation and shrinkage (see Daugherty et al 2015; Daugherty and Raz 2015). …”
Section: 0 Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations